2008
DOI: 10.1080/00016340802380750
|View full text |Cite
|
Sign up to set email alerts
|

B‐Lynch suture for massive persistent postpartum hemorrhage following stepwise uterine devascularization

Abstract: B-Lynch technique appears to be an effective procedure with a relatively low morbidity to control persistent severe PPH following a failure of vessel ligation before considering hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 28 publications
(56 reference statements)
0
59
0
4
Order By: Relevance
“…The policy management for PPH has been reported previously. 7,8,27 Digital subtraction angiography was performed using a right-sided unifemoral approach. After aortography to determine anatomy and to locate possible extravasation of contrast agent, selective catheterisation of the uterine artery or anterior trunk of the hypogastric artery was performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The policy management for PPH has been reported previously. 7,8,27 Digital subtraction angiography was performed using a right-sided unifemoral approach. After aortography to determine anatomy and to locate possible extravasation of contrast agent, selective catheterisation of the uterine artery or anterior trunk of the hypogastric artery was performed.…”
Section: Methodsmentioning
confidence: 99%
“…8 Primary long-term studies suggest that uterine-sparing surgical procedures do not appear to impair subsequent fertility and pregnancy outcomes. [7][8][9][10] Previous studies of women undergoing embolisation have suggested that it does not impair subsequent fertility, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] but the cohort, methodology and follow-up rate of these small case series are limited. 25 Moreover, in the majority of case series, no information is available regarding women with presumed preserved fertility and desire for pregnancy who do not become pregnant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success rate of this suture is 86.4% in avoiding obstetric hysterectomy and thus this suture are widely recommended for atonic PPH. 4 Successful pregnancies have been reported after B-Lynch suture. These uterine compression sutures can cause complication like hematometra, pyometra, asherman's syndrome, uterine necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of B-lynch suture is that it appears to be an effective to control severe persistent PPH following failure of vessel ligation before considering obstetric hyterectomy. 4 To date only few complications of this procedure have been reported. We would like to report a case of B-Lynch suture which caused erosion and necrosis of the uterine wall resulting in peritonitis with sepsis identified on day 16 postpartum.…”
Section: Introductionmentioning
confidence: 99%